Me, my, more, must: a values-based model of reflection. Issue 2 (4th March 2017) - Wareing, Mark
Abstract: This paper will describe the theoretical and conceptual framework that underpins a new model of reflection designed for health and social care students in practice-based learning settings and qualified professionals engaged in work-based learning. The Me, My, More, Must approach has been designed to help learners consider who they are and what impact their values might have before a description of the particular experience, situation or incident. The paper outlines the influence of movements that have emerged to support the adoption of values-based approaches to clinical practice and the development of values-based reflection. A values-based approach to the delivery of healthcare has emerged in response to several high-profile 'moral catastrophes', such as the public inquiry led by Sir Robert Francis QC which described poor standards of care at Stafford Hospital; and the abuse inflicted on residents at the Winterbourne View unit. Re-conceptualisations of the purpose of reflection and initiatives such as the 6Cs (compassion, caring, communication, competence, courage and commitment) are influencing a post-Francis era where values are not only determining selection and recruitment of students and staff, but the nature of practice through the emergence of values-based reflection.